PENGARUH PEMBERIAN MAKANAN JUNK FOOD TERHADAP KUALITAS GIZI ANAK USIA 4-5 TAHUN DI KECAMATAN KOTA BARU - Anggraeni, Dita; Rochimah, Nur; Darmiyanti, Astuti (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to find out the influence of giving junk food on the nutritional quality of children aged 4-5 years, and also to find out whether there is an influence of junk food on the nutritional quality of children, as well as finding out what treatment is given to deal with the understanding of consuming junk food. This research was conducted in Kota Baru District in 2023. The method used in this research was quantitative ex post facto. The research subjects were 96 children aged 4-5 5 years. Data was collected through data collection techniques in the form of identity questionnaires and junk food frequency questionnaires, and measuring height, weight and head circumference documentation. The results of the research show that there is an influence in providing junk food on the quality of children's nutrition. The causal factors are divided into 2, namely internal and external factors such as family environmental factors, home environment. And the treatment given can be seen from the provision of food by parents, such as bringing healthy supplies and teachers who help in providing an understanding of junk food, learning activities at school.